A indústria mineral do estado do Pará: inserção no mercado mundial e repercussões regionais - ENRÍQUEZ, Maria Amélia Rodrigues da Silva (Universidade Estadual de Campinas, 2018)
The world's mineral industry and market have undergone great changes in the last two decades, which have brought deep concems to the mineral exporting regions. The Pará State, in the northem part of Brazil, became an important mineral producer in the 80's with high leveI of participation of mineral commodities in its exportation and growing mineral reveneus, expressed in terms of GDP and fiscal taxo This work analyses the participation of Pará State's mineral exports in the world market; the related social, economic and environmental impact of the industry; and the (in)adeqacy of the industry to the fulfilment of regional expectation of development.